Fluoroquinolones and glucocorticoids as risk factors for cranial cruciate ligament disease in Retrievers - Bunch, Jessica; KuKanich, Kate; Kilian, Jimena; Korsberg, Alexa; KuKanich, Butch; Martinez, Steven (Frontiers in Veterinary Science, 2025)
ObjectiveThis study aimed to determine if a higher proportion of Retrievers with cranial cruciate ligament disease (CCLD) had previous systemic exposure to fluoroquinolones or glucocorticoids compared to Retrievers without CCLD.AnimalsClient-owned, Labrador and Golden Retrievers and Retriever crosses, aged 2–12 years old, were enrolled from Kansas State University and Washington State University with CCLD (cases) and without CCLD (nCCLD; healthy controls).MethodsThe study was designed as a retrospective, multi-institutional case–control study. Medical records (2019–2023) were reviewed for systemic and topical exposure to fluoroquinolones or glucocorticoids within 6 months of CCLD exam or visit (nCCLD) or anytime throughout life prior to injury or visit. Data were analyzed using univariate and multivariate logistic regression analyses. The results were reported as coefficients, standard errors, p-values, and odds ratios with 95% confidence intervals. A p-value of <0.05 was considered significant.ResultsA total of 419 dogs (216 cases and 203 controls) were enrolled in this study. The odds ratios of CCLD after systemic fluoroquinolone exposure were three times (CI: 1.01–8.90) higher than the odds ratios of CCLD without fluoroquinolone exposure. The odds ratios of CCLD after systemic glucocorticoid exposure were 3.51 times (CI: 1.94–6.37) higher than the odds ratios of CCLD without glucocorticoid exposure. Topical administration was not found to pose the same risk.ConclusionThe findings of this study suggest that the administration of systemic fluoroquinolones or systemic glucocorticoids was identified as a risk factor for the development of CCLD in Retriever breeds. Prospective studies are needed.Clinical relevanceAlthough not all risk factors for CCLD can be mitigated, systemic fluoroquinolones and/or glucocorticoids should be used cautiously in Retriever breeds.